Last of the blasts: celebrating the Carrie Furnaces' legacy through creative adaptive reuse - Voigt, Emilee R. (Kansas State University, 2019)
The United States holds a rich industrial history that is still seen today from architecture and the sites that hold them. Most of these sites have already been demolished, but a small number do remain. For those that remain, they are vacant, underused and most likely a brownfield. These sites have the opportunity to be used by people again as outdoor public spaces. Pre-World War II industrial factories hold a piece of the history of the United States and can be given to the people once more. This report focuses on the Carrie Furnaces, a longstanding steel production factory in the suburbs of Pittsburgh, Pennsylvania. The site represents Pittsburgh’s steel production era of the late 1800s and early 1900s and has become local, national and international artists’ inspirations since the early 1990s. After the furnaces became a designated National Historic Landmark, a rich 20-acre landscape is left that surrounds the beautiful industrial architecture. Through the use of precedent studies, interviews and site inventory, a well-versed projective design will be produced. This report will analyze five industrial landscape precedents based on project scale, designer, previous use of the site, contamination history and more. The interviews will take place with two individuals who have worked on and with the Carrie Furnaces for the past 20 years. This report will gear questions towards understanding their personal experiences with the site and their hopes for the future. A thorough site inventory and analysis will be conducted, exploring existing conditions at the regional and site scale. Site analysis at the site scale will include site identity, site inventory, diagramming and opportunities, and constraints. From utilizing these methods, a projective design can show the future growth of the Carrie Furnaces through programmed spaces and economic opportunities that bring the history and space back to the people of suburban Pittsburgh.
Keywords: Adaptive reuse; Post-industrial; Brownfield; Carrie Furnaces